Full‐Color Electrophoretic Display Using Charged Colloidal Arrays of Core–Shell Microspheres with Enhanced Color Tunability in Non‐Polar Medium. Issue 21 (20th August 2021) - Park, Eunseon; Lee, Seungju; Lee, Hyunjung; Lee, Wonmok
Abstract: In this study, core–shell microspheres of poly(methylmethacrylate) (PMMA) and poly(t‐butylmethacrylate) (PtBMA) are synthesized and dispersed in a non‐polar medium exhibiting a structural color in the visible range. The charge stabilization of the PMMA–PtBMA microsphere is achieved because of preferential adsorption of the charged inverse micelles of aerosol‐OT (AOT) on the microsphere surface. While the PtBMA shell enables the dispersion of the microspheres in isoparaffinic fluid, the PMMA core provides an enhanced refractive index contrast with the medium. In comparison to PtBMA‐only microsphere, incorporation of PMMA core not only increases the average refractive index but also increases the surface charge density of the microsphere, which is attributed to strong attraction between the inverse micelles and the microsphere. The optimized crystalline colloidal array (CCA) of the PMMA–PtBMA microsphere shows stronger structural colors than those of the PtBMA‐only spheres because of an enhanced index contrast with the liquid medium, and an improved color tunability is also achieved. A CCA exhibits approximately 50% light transmittance, demonstrating a semi‐transparent display. The repeated voltage biases proved that a CCA has excellent stability. Finally, a low‐angular dependency of the PMMA–PtBMA CCA is confirmed, which is an advantageous feature as an electrophoretic display. Abstract : An electrophoretic display with full‐color tunability is demonstrated using colloidal arrays of poly(methylmethacrylate) (PMMA)–poly(t‐butylmethacrylate) core–shell microspheres in liquid paraffin. Colloidal stability is provided by the charged aerosol‐OT (AOT) micelles adsorbed on the microsphere surface in which high index PMMA core assures a strong van der Waals interaction with AOT micelles to result in high zeta potential and excellent color tunability.